1997
DOI: 10.1162/003355397555325
|View full text |Cite
|
Sign up to set email alerts
|

Large Shareholders, Monitoring, and the Value of the Firm

Abstract: We propose that dispersed outside ownership and the resulting managerial discretion come with costs but also with bene ts. Even when tight control by shareholders is ex post ef cient, it constitutes ex ante an expropriation threat that reduces managerial initiative and noncontractible investments. In addition, we show that equity implements state contingent control, a feature usually associated with debt. Finally, we demonstrate that monitoring, and hence ownership concentration, may con ict with performance-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
627
1
14

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,268 publications
(697 citation statements)
references
References 31 publications
(35 reference statements)
31
627
1
14
Order By: Relevance
“…We assume that the strategic decision to acquire equity in a rival belongs to the dominant controlling shareholder of one company in the industry who may already hold outside toeholds. We find that, maximizing his own wealth, this shareholder may engage Panunzi (1997) or Bolton and Von Thadden (1998) for a theoretical approach, and La Porta, Lopez-Silanes, Shleifer and Vishny (2002) for a discussion of the role of the large shareholder. 7 The fact that, within groups of firms, some categories of shareholders may be favored at the expense of others has long been acknowledged by the finance literature.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…We assume that the strategic decision to acquire equity in a rival belongs to the dominant controlling shareholder of one company in the industry who may already hold outside toeholds. We find that, maximizing his own wealth, this shareholder may engage Panunzi (1997) or Bolton and Von Thadden (1998) for a theoretical approach, and La Porta, Lopez-Silanes, Shleifer and Vishny (2002) for a discussion of the role of the large shareholder. 7 The fact that, within groups of firms, some categories of shareholders may be favored at the expense of others has long been acknowledged by the finance literature.…”
Section: Introductionmentioning
confidence: 83%
“…The "favorite" effect 17 For instance, when A holds shares in only three firms, say 1, 2 and 3, and A controls firm 1 only, C = {1},…”
Section: The Different Effects At Playmentioning
confidence: 99%
“…E mail: joatribo@emp.uc3m.es 1 Examples of seminal papers are Berle and Means (1932), Jensen and Meckling (1976), Grossman and Hart (1980), Schleifer and Vishny (1986) and Burkart et al (1997). 2 Barclay and Holderness (1989), Barclay et al (1993) and Zingales (1994) measure private benefits indirectly by showing that large blocks of ownership that confer voting rights sell at a premium.…”
Section: Introductionmentioning
confidence: 99%
“…Various theoretical studies (e.g., Shleifer and Vishny (1997), have indicated that for block holders, the incentive to monitor managers increases with increase of stakes in terms of ownership. This reduces the problem of free-rider associated with dispersed shareholding (Hart, 1995a;Burkart et al, 1997). Further, as compared to dispersed share holders, large shareholders are in a better position to take concerted action against managers.…”
Section: Ownership Structurementioning
confidence: 98%